2005
DOI: 10.1086/497438
|View full text |Cite
|
Sign up to set email alerts
|

Promoter and 3′-Untranslated-Region Haplotypes in the Vitamin D Receptor Gene Predispose to Osteoporotic Fracture: The Rotterdam Study

Abstract: Polymorphisms of the vitamin D receptor gene (VDR) have been shown to be associated with several complex diseases, including osteoporosis, but the mechanisms are unknown and study results have been inconsistent. We therefore determined sequence variation across the major relevant parts of VDR, including construction of linkage disequilibrium blocks and identification of haplotype alleles. We analyzed 15 haplotype-tagging SNPs in relation to 937 clinical fractures recorded in 6,148 elderly whites over a follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
297
3
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(328 citation statements)
references
References 37 publications
18
297
3
10
Order By: Relevance
“…This polymorphism has been associated with fracture in other populations, but not with BMD (Fang et al 2003). The most comprehensive study of VDR alleles in relation to osteoporosis-related phenotypes was that of Fang et al (2005), who conducted a large-scale study of haplotype tagging SNP of VDR in 6418 participants of the Rotterdam study. As the result of this analysis, the authors identified haplotype alleles in the promoter region and 3Ј untranslated region (UTR) that were associated with an increased risk of fracture.…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…This polymorphism has been associated with fracture in other populations, but not with BMD (Fang et al 2003). The most comprehensive study of VDR alleles in relation to osteoporosis-related phenotypes was that of Fang et al (2005), who conducted a large-scale study of haplotype tagging SNP of VDR in 6418 participants of the Rotterdam study. As the result of this analysis, the authors identified haplotype alleles in the promoter region and 3Ј untranslated region (UTR) that were associated with an increased risk of fracture.…”
Section: Vitamin D Receptor (Vdr)mentioning
confidence: 99%
“…Several polymorphisms in the gene encoding the VDR, such as Cdx2, FokI, BsmI, ApaI, and TaqI, have been demonstrated to be related to bone characteristics and risk of fractures, although results remain equivocal (4)(5)(6). Moreover, specific combinations of these polymorphisms, so-called haplotypes, have been identified as a risk factor for fractures (7). Beside effects on bone metabolism, VDR polymorphisms, in particular BsmI, are associated with cardiovascular risk factors such as increased blood pressure, an unfavorable lipid profile (8,9), increased left ventricular mass in hemodialysis patients (10), and intimal medial thickening of the carotid artery (11).…”
Section: Introductionmentioning
confidence: 99%
“…(17,25) We studied whether carrying VDR block 5 haplotype 1 in LPH C-homozygotes would influence the observed associations because both genes are involved in intestinal calcium handling. A study by Obermayer-Pietsch and colleagues (33) found intestinal calcium uptake to be impaired in lactose-intolerant subjects when calcium was administered concomitantly with lactose.…”
Section: Discussionmentioning
confidence: 99%
“…VDR genotypes in the 3' UTR region were determined, and haplotype blocks were constructed as described in detail by Fang and colleagues. (25) To address the possibility of genotyping errors, 5% of the Rotterdam Study and the LASA was regenotyped for the LPH T-13910C polymorphism.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation